Meningkatkan Nilai-Nilai Religius Anak Melalui Pendampingan Pembelajaran Al-Quran di TPQ Sabilil Huda Desa Bedingin, Ponorogo - Rinesti Witasari; Khoirul Fathoni; Ibrotuli Ulil Albab (CV. Adiguna Kertosari, 2022)
Learning the Qur'an is very important, especially for children. In this activity, developing a sense of love for the Qur'an, the learning of the Qur'an should be instilled from an early age so that when they are old they are able to carry out the religious values ​​contained in the Qur'an in their daily lives. Al-Qur'an learning in the Bedingin village environment is said to be very lacking due to lay parents who do not understand the Qur'an, as well as the lack of educators to teach al-Qur'an learning, and also the lack of adequate places for learning the Qur'an. the. Emerged from the enthusiasm and enthusiasm of children to learn the Koran and the importance of learning the Koran is taught. This KPM activity contributes to children by providing learning and knowledge about the importance of the Qur'an to be studied and practiced in everyday life. By doing this activity, we get positive support and attention from the local community. The result of this activity is that many children are enthusiastic and enthusiastic in learning the Koran, increasing knowledge and knowledge about the Qu’ran for children.